Early introduction of foods to prevent food allergy - Chan, Edmond S. (Allergy Asthma Clin Immunol, 2018)
Food allergy is a growing public health problem, and in many affected individuals, the food allergy begins early in life and persists as a lifelong condition (e.g., peanut allergy). Although early clinical practice guidelines recommended delaying the introduction of peanut and other allergenic foods in children, this may have in fact contributed to the dramatic increase in the prevalence of food allergy in recent decades. In January 2017, new guidelines on peanut allergy prevention were released which represented a significant paradigm shift in early food introduction. Development of these guidelines was prompted by findings from the Learning Early About Peanut Allergy study—the first randomized trial to investigate early allergen introduction as a strategy to prevent peanut allergy. This article will review and compare the new guidelines with previous guidelines on food introduction, and will also review recent evidence that has led to the paradigm shift in early food introduction.